Ebola virus disease: an update on post-exposure prophylaxis. Issue 6 (June 2018) - Fischer, William A; Vetter, Pauline; Bausch, Daniel G; Burgess, Timothy; Davey, Richard T; Fowler, Robert; Hayden, Frederick G; Jahrling, Peter B; Kalil, Andre C; Mayers, Douglas L; Mehta, Aneesh K; Uyeki, Timothy M; et al.
Summary: The massive outbreak of Ebola virus disease in west Africa between 2013 and 2016 resulted in intense efforts to evaluate the efficacy of several specific countermeasures developed through years of preclinical work, including the first clinical trials for therapeutics and vaccines. In this Review, we discuss how the experience and data generated from that outbreak have helped to advance the understanding of the use of these countermeasures for post-exposure prophylaxis against Ebola virus infection. In future outbreaks, post-exposure prophylaxis could play an important part in reducing community transmission of Ebola virus by providing more immediate protection than does immunisation as well as providing additional protection for health-care workers who are inadvertently exposed over the course of their work. We propose provisional guidance for use of post-exposure prophylaxis in Ebola virus disease and identify the priorities for future preparedness and further research.